Analisis Faktor yang Mempengaruhi Kejadian Nyaris Cedera di Rumah Sakit di Indonesia: Kajian Literatur - Pratiwi, Rika Meylina; Dhamanti, Inge (Jurnal Kesehatan Komunitas, 2025)
Background: The percentage of incidents recorded as KNC in Indonesia was 47.6%, higher than the percentage of incidents reported as KTD, which was 46.2%. One important effort in patient safety is to reduce Near Miss Events (NME), which can avoid serious injury to patients that impact the services provided. Aim: This study aims to identify factors that influence Near Miss Events in hospitals in Indonesia. Method: The study used a literature review method. Search with Garuda, Semantic Scholar, and Google Scholar databases. The article criteria were research conducted in Indonesia, publications in 2014 - 2024, full text, free access, original articles and an explanation of NME in them. Results: The search resulted in 6 articles that met the criteria and were then analyzed based on Donabedian's Theory. The research findings showed that in the structure factor, the competence of medical personnel and work environment conditions were significant factors. In the process factor, team communication and compliance with SOPs influenced the risk of NME. The outcome factor showed that NME had an impact on decreasing patient trust and service quality. Conclusion: The occurrence of KNC in hospitals in Indonesia is influenced by structural, process, and outcome factors, it is necessary to focus on improvements in hospital management, staff training, improving medical team communication, and implementing a patient safety culture to reduce the risk of recurrence of such incidents.